2023
DOI: 10.1039/d3gc01446k
|View full text |Cite
|
Sign up to set email alerts
|

A “three-in-one” strategy based on an on-demand multifunctional fluorescent amphoteric polymer for ecological leather manufacturing: a disruptive wet-finishing technique

Chao Wei,
Xuechuan Wang,
Siwei Sun
et al.

Abstract: The traditional wet-finishing process for leather manufacturing is complicated and uses numerous chemical additives, limiting the leather industry's development in the direction of energy saving and emission reduction. Integrated with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The molecular weights (Mn) and PDI of PAMLD-1 (Figure f) are 40350 g/mol and 2.2, respectively. Compared with the reported amphoteric retanning and fatliquoring agents (Mn = 219430, PDI = 1.5), the PAMLD exhibits smaller molecular weights and wider molecular weight distribution. Similarly, the average particle size of PAMLD emulsion (∼325 nm, Figure S3) is smaller than that of commercially amphoteric retanning agent FRA (∼356 nm, Figure S4).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…The molecular weights (Mn) and PDI of PAMLD-1 (Figure f) are 40350 g/mol and 2.2, respectively. Compared with the reported amphoteric retanning and fatliquoring agents (Mn = 219430, PDI = 1.5), the PAMLD exhibits smaller molecular weights and wider molecular weight distribution. Similarly, the average particle size of PAMLD emulsion (∼325 nm, Figure S3) is smaller than that of commercially amphoteric retanning agent FRA (∼356 nm, Figure S4).…”
Section: Resultsmentioning
confidence: 84%
“…11 More recently, amphoteric acrylic polymers with dual functions of retanning and fatliquoring have been reported for chrome-free tanning systems to reduce the processing time and save leather chemicals. 12 In the methods of Ma et al 13,14 and Liu et al, 15 cationic monomers are synthesized through the Mannich reaction or quaternization reaction and then copolymerized with acrylic monomers via free radical polymerization to prepare the amphoteric polymer. Unfortunately, the approach requires a two-step reaction in an Herein, we propose a novel and feasible approach to synthesize amphoteric acrylic polymer (abbreviated as PAMLD) by free radical polymerization using acrylic acid (AA), methacrylic acid (MAA), dodecyl 2-methyl acrylate (LMA), and ethyl methacrylate trimethylammonium chloride (DMC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anionic dyes offer several advantages, such as excellent color fastness and vibrant hues, making them ideal for achieving the desired visual appeal in leather products. , However, anionic dyes are not suitable for all types of tanned leathers. Especially in the case of organic tanning process, during the post-tanning process, poor available amino groups in crust leather results in poor dye penetration and reduced color intensity . According to research by Salt, anionic dyes tend to exhibit poor exhaustion rates on vegetable-tanned leathers, leading to increased water consumption and dye wastage .…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al reported on the use of pADD-DMENA amphoteric polymers as retanning agents, which exhibited a uniformly bright-yellow surface and demonstrated superior lightfastness, durability, and washability. Similarly, Ding et al reported on the utilization of a biomass-derived aldehyde tanning agent (BAT-iDP) in leather processing, , leading to in situ dyeing properties.…”
Section: Introductionmentioning
confidence: 99%